KARAKTER EROPA PADA RUMAH TINGGAL SAUDAGAR BATHIK DI LAWEYAN SURAKARTA - Tri Joko Daryanto (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
Laweyan village has existed since the beginning of Nagari Surakarta Hadiningrat in1745. It is such as a village ofbathik merchant with specific architecturalcharacteristics. The character forms a merger of many architectural styles, which isdominated by Europhean (Western) style whithout disapearing Javanese architecturalcharacteristics.In order to understand the using of European architectural elements, the research isperformed by naturalistic approach. The samples and themes are defined on the fieldpurposively. The finding of the themes is connected inductively in order to get theideographic construction as localfinding. ,The research founds the using ofgolden section in defining building sshape proportionand arranging its facade composition. The European forms and ornaments consist ofArtdeco, Art nouveau, Greek and Indies which are merged in Javaneseformat eclectically.There is tendency that European forms and ornaments arefound in the roomsor part ofbuilding with visual continuity positions.